2012
DOI: 10.1371/journal.ppat.1003099
|View full text |Cite
|
Sign up to set email alerts
|

Statins Decrease Neuroinflammation and Prevent Cognitive Impairment after Cerebral Malaria

Abstract: Cerebral malaria (CM) is the most severe manifestation of Plasmodium falciparum infection in children and non-immune adults. Previous work has documented a persistent cognitive impairment in children who survive an episode of CM that is mimicked in animal models of the disease. Potential therapeutic interventions for this complication have not been investigated, and are urgently needed. HMG-CoA reductase inhibitors (statins) are widely prescribed for cardiovascular diseases. In addition to their effects on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 76 publications
5
89
2
Order By: Relevance
“…A treatment with lovastatin 20 mg/kg alone significantly ameliorated the signs of neuro-inflammation and prolonged the lifespan of the mice by 2 days in line with previous published reports. 2,17 The administration of simvastatin 20 mg/kg alone, a statin that, like lovastatin, inhibits endogenous cholesterol production by competitive inhibition of HMG-CoA reductase, failed to protect against ECM (Fig. 1A), confirming previous studies.…”
Section: Lovastatin Potentiates the Protective Activity Of Vegf Againsupporting
confidence: 84%
See 1 more Smart Citation
“…A treatment with lovastatin 20 mg/kg alone significantly ameliorated the signs of neuro-inflammation and prolonged the lifespan of the mice by 2 days in line with previous published reports. 2,17 The administration of simvastatin 20 mg/kg alone, a statin that, like lovastatin, inhibits endogenous cholesterol production by competitive inhibition of HMG-CoA reductase, failed to protect against ECM (Fig. 1A), confirming previous studies.…”
Section: Lovastatin Potentiates the Protective Activity Of Vegf Againsupporting
confidence: 84%
“…This is in agreement with the ability of statins to reduce iNOS expression, thereby protecting neuronal cells, while increasing endothelial NOS expression and increasing microcirculatory blood flow via local vasodilatation. 2,19 However, not all statins share the same protective properties. Simvastatin and lovastatin are both known to inhibit HMG-CoA reductase but simvastatin does not exert the same protective activity against ECM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that statins alter the natural course of other parasitic diseases such as cerebral malaria and intestinal toxoplasmosis (19,20). In addition, there is evidence that simvastatin decreases cardiac inflammation and fibrosis in dogs chronically infected with T. cruzi (21).…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have shown that eNOS is impaired during systemic infection, which leads to brain microcirculation dysfunction [46][47][48]. We showed that during different infectious diseases, there is a functional capillary rarefaction (Figure 3) that can be caused by the impairment of endothelial NO production by a reduction of eNOS activity or by reduced levels of the enzyme cofactor tetrahydrobiopterin-BH4 [49].…”
Section: As Shown Inmentioning
confidence: 78%
“…Interestingly, in experimental models of malaria [48] and sepsis (Reis et al, submitted) blood flow was recovered by treatment with statins. As reviewed by Giannopoulos et al [54], statins are shown to enhance eNOS expression and can contribute to the restoration of brain capillary function.…”
Section: As Shown Inmentioning
confidence: 99%